Pengaruh Model Course Review Horay Berbantuan Tabel Perkalian terhadap Pemahaman Matematis Siswa Kelas III SD - Saleha, Zahra; Maulana, Maulana; Sunaengsih, Cucun (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
Understanding mathematical concepts is a skill in interpreting a mathematical concept using one's own language. It refers to the ability of students to explain a mathematical concept. In terms of understanding mathematical concepts, students still struggle with grasping the concept and properties of multiplication. This study aims to investigate whether the Course Review Horay learning model affects the mathematical concept understanding of third-grade elementary school students. The research employs an experimental method with a quasi-experimental design using nonequivalent control groups. The respondents in this study were 60 students, with 30 students in the experimental group and 30 students in the control group. The results indicate that there is an effect of the Course Review Horay learning model on the mathematical concept understanding of third-grade elementary school students, specifically regarding the properties of multiplication. This is evidenced by the gain in pre-test and post-test scores being 0.69, which falls into the moderate category, indicating an improvement in understanding after using the Course Review Horay model with multiplication tables.